A method for preparing colored heat-insulating sun-proof glass coating

By using copper-zinc cesium ion co-doped tungsten oxide/graphene composite multifunctional thermal insulation powder and PMMA polymer spherical particles to wrap color pigments, the color attenuation and thermal insulation function of color insulation coatings are solved, and the antibacterial and antiviral performance is improved through the addition of graphene, achieving efficient heat insulation, rapid heat dissipation and weather resistance.

CN116463043BActive Publication Date: 2025-04-08JUZHI (SUZHOU) NANOTECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310508111.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-08
Publication Date
2025-04-08
Estimated Expiration
2043-05-08

AI Technical Summary

Technical Problem

The existing color thermal insulation coatings have problems such as color attenuation, thermal insulation function attenuation, slow heat dissipation and insufficient antibacterial and antiviral performance.

Method used

Co-doped tungsten oxide/graphene composite multifunctional thermal insulation powder is used to encapsulate color pigments and organic ultraviolet absorbers through swollen PMMA polymer spherical particles, which improves the color weather resistance and heat dissipation performance of the coating, and enhances the antibacterial and antiviral properties through the addition of graphene.

Benefits of technology

The coating is achieved without fading, antibacterial and antiviral, high heat dissipation, high heat insulation and high weather resistance, and has a wider application prospect compared with traditional glass thermal insulation coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116463043B_ABST
    Figure CN116463043B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a colored heat-insulating sunscreen glass coating: first, a copper-zinc-cesium ion co-doped tungsten oxide / graphene composite heat-insulating powder is prepared, and then a high-polarity dispersant, an alcohol-soluble grinding resin, and a solvent are used to coat the composite heat-insulating powder on the surface and grind it to form a heat-insulating slurry; then the colored powder is ground into a transparent colored pigment dispersion liquid with a dispersant, an organic solvent, a pigment synergist, and a grinding resin, an organic ultraviolet absorber is added, and then the swollen PMMA polymer spherical particles are used to uniformly wrap the colored pigment and the organic ultraviolet absorber as color-adjusting particles; finally, the heat-insulating slurry, the color-adjusting particles, the special resin, the adhesion promoter, the wetting agent, the graphene composite antiviral slurry, and the diluent are stirred and mixed to form a colored heat-insulating coating liquid. The coating liquid is applied on the glass to prepare a coating, which has the characteristics of non-fading, antibacterial and antiviral, high heat dissipation, high heat insulation, and high weather resistance, and has a wide range of application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano functional coating preparation, and in particular relates to a method for preparing a colored heat-insulating sun-proof glass coating. Background Art

[0002] It is reported that building energy accounts for about 30% of the total domestic energy consumption, and most of this energy comes from high-carbon thermal power generation. In theory, building glass thermal insulation coating can block the heat input of infrared rays from sunlight without affecting the entry of visible light. It is a kind of building energy-saving glass. The temperature difference between indoor and outdoor glass with thermal insulation and sunscreen coating can reach 5-15℃, which significantly improves human comfort and reduces air conditioning cooling capacity in summer. Theoretically calculated energy-saving efficiency can reach 20-35%. It can be widely used in glass top floors of high-speed railway stations, office buildings, science and technology museums and other public building glass halls and other places, contributing to the realization of the country's "carbon peak and carbon neutrality" goals.

[0003] Chinese patent CN 102391778A proposes a colored transparent heat-insulating glass coating and a preparation method thereof, which uses traditional ATO slurry as the heat-insulating material and directly uses transparent color slurry to adjust the color. The heat-insulating coating prepared in this way is the same as the colored heat-insulating coating liquid products currently sold on the market. There are generally a series of problems such as single function, serious attenuation of heat-insulating function, slow heat dissipation and color attenuation.

[0004] Therefore, it is urgent to provide a multifunctional heat-insulating coating with a long-lasting heat-insulating function, non-fading color, and fast heat dissipation. The present invention adopts a new material preparation process to prepare a copper-zinc-cesium ion co-doped tungsten oxide / graphene composite multifunctional heat-insulating powder to solve the above problems. First, the swollen PMMA polymer spherical particles uniformly wrap the color pigment and the organic ultraviolet absorber as color adjustment particles, which solves the problem of color attenuation of the coating. Then, the graphene in the copper-zinc-cesium ion co-doped tungsten oxide / graphene composite heat-insulating powder, and the graphene in the graphene composite antiviral slurry added as an antiviral additive, jointly construct and enhance the carrier characteristics of the composite material, so that the infrared heat energy absorbed by the coating can be quickly dissipated into the air in the form of radiation heat dissipation, avoiding the accumulation of the coating surface temperature and the transmission to the room to solve the problem of continuous heating of the existing coating surface. The colored heat-insulating sunscreen glass coating has the characteristics of non-fading, antibacterial and antiviral, high heat dissipation, high heat insulation and high weather resistance, and has a wide range of application prospects compared to traditional glass heat-insulating coatings. Summary of the invention

[0005] The present invention provides a method for preparing a colored heat-insulating sun-proof glass coating, and the specific steps are as follows:

[0006] 1) Preparation of copper-zinc-cesium ion co-doped tungsten oxide / graphene composite thermal insulation powder: firstly, copper salt, zinc salt, cesium iodide and ammonium metatungstate are weighed, added into a certain mass of ammonia solution with pH=9, ultrasonically stirred for a certain time, a reducing dispersant is added, and then graphene oxide powder is added, and ultrasonic stirring is continued for a certain time to obtain a precursor solution, and the precursor solution is transferred to a reactor and heated and kept warm at a certain temperature for a certain time, cooled naturally, filtered, and washed to obtain copper-zinc-cesium co-doped tungsten oxide / graphene composite thermal insulation powder;

[0007] 2) Preparation of copper-zinc-cesium ion co-doped tungsten oxide / graphene composite thermal insulation slurry: using a high-polarity dispersant, an alcohol-soluble grinding resin, and a solvent, the composite thermal insulation powder is surface coated and ground to form a composite thermal insulation slurry;

[0008] 3) Preparation of color-adjusting particles: compounding an inorganic color powder with an organic color powder, adding dispersant A, dispersant B, an organic solvent, a pigment synergist, and a grinding resin to grind into a transparent color pigment dispersion, then adding an organic ultraviolet absorber, dissolving and mixing, and then uniformly wrapping the color pigment and the organic ultraviolet absorber with PMMA polymer swelled with a swelling agent, heating to a certain temperature in an ultrasonic wave and swelling for a certain time, rotary evaporating the solvent, washing with ethanol, and vacuum drying to obtain color-adjusting particles with ultraviolet absorption function;

[0009] 4) finally, the copper-zinc-cesium co-ion-doped tungsten oxide / graphene composite thermal insulation slurry, color adjustment particles, special resin, adhesion promoter, wetting agent, graphene composite antiviral slurry, and diluent are stirred and mixed evenly, sieved, and prepared into a colored thermal insulation coating liquid;

[0010] 5) Apply the prepared colored heat-insulating coating liquid to the clean glass surface with a high-density sponge brush under certain temperature and humidity requirements. After it is completely cured, a colored heat-insulating sun-proof glass coating can be obtained.

[0011] Preferably, the expression of step 1) copper-zinc-cesium co-doped tungsten oxide is Cu a Zn b Cs c W 1-a-bO3, wherein 0<a≤0.1, 0<b≤0.1, 0.3≤c≤0.4; the mass ratio of the total weight of copper salt, zinc salt, cesium iodide and ammonium metatungstate, pH=9 ammonia solution, reducing dispersant and graphene oxide powder is 1:3:0.1:(0.001~0.005); the copper salt is one of copper acetate, copper nitrate and copper sulfate; the zinc salt is one of zinc acetate, zinc nitrate and zinc sulfate; the ultrasonic stirring time is 30~60min; the reducing dispersant is one of polycaprolactone polyol-polyethyleneimine block copolymer, polyvinyl pyrrolidone and polymer polyol; the continued ultrasonic stirring time is 60~120min; the heating temperature of the reactor is 180~300℃, and the heat preservation is 12~24h.

[0012] Preferably, in the step 2), the high polarity dispersant is one or a combination of polymer dispersants SN-2301, Tech-5011 and SN-1008A with acidic groups; the alcohol-soluble grinding resin is one or a combination of alcohol-soluble rosin resin, alcohol-soluble maleic acid resin, alcohol-soluble aldehyde-ketone resin; the solvent is one of ethanol and propylene glycol methyl ether; the mass ratio of the composite thermal insulation powder, dispersant, grinding resin and solvent is (20-30): (4-9): (10-15): 50; the zirconium beads are selected to have a diameter less than 0.1 mm and a sanding linear speed less than 13 m / s.

[0013] Preferably, in step 3), the inorganic nano colored powder is one of carbon black, cobalt blue, iron oxide red and iron oxide yellow; the organic colored powder is one of phthalocyanine blue, quinacridone red and permanent yellow; the dispersant A is one of BYK110, BYK-2095 and Tech-5010; the dispersant B is one of Tech-5080, UNIQJET 9510 and BYK161; the organic solvent is one of ethyl acetate, butanone and ethanol; the pigment synergist is one of Tech-5522 and Tech-5550; the grinding resin is one of polyamide resin and aldehyde-ketone resin; the mass ratio of the inorganic nano colored powder, the organic colored powder, the dispersant A, the dispersant B, the organic solvent, the pigment synergist and the grinding resin is (5-10): (5-10): (2-5): (2-5): 50: (0.1-0.5): (2-5); the zirconium beads are selected to have a diameter of less than 0.1 mm and a sanding line speed of less than 13 m / s; the PMMA polymer particles are selected to have a particle size of 1-2 microns; the swelling agent is one of alkylphenol polyoxyethylene ether, propylene glycol methyl ether, butanone, ethyl acetate, 4-methyl-2-pentanone, acetone, dimethyl sulfoxide or a combination thereof; the organic ultraviolet absorber is UV-928 and UV 384-2; the mass ratio of the transparent color pigment dispersion, swelling agent, PMMA polymer particles and organic ultraviolet absorber is (5-10):50:(20-50):30; in the step 3), the temperature is ultrasonically raised to 50-60°C for 4-6 hours.

[0014] Preferably, the special resin in step 4) is an alcohol-soluble silicone-modified polyurethane resin or a polysiloxane-modified resin; the adhesion promoter is one of Tech-7121 and EL-9041; the wetting agent is one of acetylene glycol wetting agents Tech-204E, Surfynol 485 and Tech-247; the graphene composite antiviral slurry is an alcohol slurry 1500E or 1515E; the diluent is one of PM and DPM or a combination thereof; the copper-zinc-cesium co-doped tungsten oxide / graphene composite thermal insulation slurry: color adjustment particles: special resin: adhesion promoter: wetting agent: graphene composite antiviral slurry: diluent = (20-30): (1-5): (30-40): (0.1-0.3): (0.1-0.3): (1-3): (10-20).

[0015] Preferably, the construction temperature in step 5) is 10-40° C., the humidity is less than 80%, the surface drying time is 30-60 minutes, and complete curing takes 7 days.

[0016] Compared with the prior art, the method for preparing a colored heat-insulating sun-proof glass coating according to the present invention has the following beneficial effects:

[0017] 1) The traditional preparation of colored glass coating is to directly mix the heat insulation slurry and the coloring slurry, which will fade when exposed to rainy weather and other bad weather outdoors for a long time. The present invention prepares PMMA particles by compounding the composite color pigment and the organic ultraviolet absorber, which solves the problem of weather resistance and fading resistance of the color pigment due to rain immersion, and at the same time improves the color of the pigment, so that it can be used outdoors for a long time without fading.

[0018] 2) Traditional glass thermal insulation coatings do not have antibacterial and antiviral functions. The present invention uses copper, zinc, and cesium ions to dope tungsten oxide and then composite it with graphene. The addition of copper and zinc co-doping and graphene network improves the antibacterial and antiviral properties of the product.

[0019] 3) Zinc doping can improve the ultraviolet absorption performance of the composite material, reduce the amount of organic ultraviolet absorber in the formula, form an inorganic and organic ultraviolet absorption synergistic effect, and at the same time, the organic ultraviolet absorber is added inside the PMMA particles, which greatly slows down the performance attenuation of the ultraviolet absorber due to environmental reasons; the composite thermal insulation powder loaded on the graphene sheet can stabilize the composite thermal insulation powder well in the final coating, and provide a strong network structure together with the resin, so that the thermal insulation function of the coating will not decay for a long time in a rainy environment.

[0020] 4) The addition of graphene in the copper-zinc-cesium ion co-doped tungsten oxide / graphene composite insulation powder and the graphene in the graphene composite antiviral slurry added at the end improve the heat dissipation and antiviral properties of the coating. At the same time, the infrared heat energy absorbed by the coating can be quickly dissipated into the air in the form of radiation heat dissipation, avoiding the accumulation of temperature on the coating surface and its transfer to the room. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a SEM image of the copper-zinc-cesium ion co-doped tungsten oxide / graphene composite thermal insulation powder according to Example 1 of the present invention.

[0022] Figure 2 TEM image of copper-zinc-cesium ion co-doped tungsten oxide / graphene composite thermal insulation slurry according to Example 1 of the present invention

[0023] Figure 3 This is the particle size distribution diagram of the copper-zinc-cesium ion co-doped tungsten oxide / graphene composite thermal insulation powder according to the second embodiment of the present invention.

[0024] Figure 4 This is the SEM image of the transparent color pigment of Example 2 of the present invention.

[0025] Figure 5 The particle size distribution diagram of the transparent color pigment of Example 4 of the present invention is DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Embodiment 1

[0028] First, a copper-zinc-cesium ion co-doped tungsten oxide / graphene composite thermal insulation powder is prepared: first, a mixture of copper acetate, zinc acetate, cesium iodide and ammonium metatungstate with a total mass of 100 g is weighed according to the molar ratio of copper, zinc, cesium and tungsten in the molecular formula of 0.01:0.01:0.3:0.98, crushed and ground evenly, and then slowly added to 300 g of ammonia solution with a pH of 9, ultrasonically stirred for 30 minutes, and then 1 g of polycaprolactone polyol-polyethyleneimine block copolymer and 0.01 g of graphene oxide powder are added, and ultrasonic stirring is continued for 60 minutes to obtain a precursor solution, and the precursor solution is transferred to a reactor and heated at 180°C for 12 hours, cooled naturally, filtered, and washed clean to obtain a copper-zinc-cesium co-doped tungsten oxide / graphene composite thermal insulation powder;

[0029] Preparation of copper-zinc-cesium ion co-doped tungsten oxide / graphene composite thermal insulation slurry: using 4g of high-polarity dispersant SN-2301, 10g of alcohol-soluble rosin resin, and 50g of ethanol; in a non-circulating explosion-proof sand mill, using 0.05mm zirconium beads and a linear speed of 12m / s, 20g of composite thermal insulation powder was surface coated and ground to prepare a composite thermal insulation slurry with a D90 of less than 120 nanometers;

[0030] Preparation of color adjustment particles: 5g of inorganic cobalt blue powder and 5g of phthalocyanine blue were compounded, 2g of dispersant BYK110, 2g of dispersant Tech-5080, 50g of ethyl acetate, 0.1g of pigment synergist Tech-5550, and 2g of polyamide resin were added, and ground into a transparent color pigment dispersion in a non-circulating explosion-proof sand mill using 0.05mm zirconium beads at a linear speed of 12m / s; then 396g of organic ultraviolet absorber was added. UV-928, dissolved and mixed, and then swelled with 661g of butanone, the PMMA polymer spherical particles with a particle size of 1μm and a mass of 265g were used to evenly wrap the color pigment and the organic ultraviolet absorber, heated to 50°C in ultrasound, maintained for 4h, and the solvent was evaporated by rotary evaporation, cleaned with ethanol, and vacuum dried to obtain color adjustment particles with ultraviolet absorption function;

[0031] Finally, 20g of copper-zinc-cesium ion co-doped tungsten oxide / graphene composite insulation slurry, 1g of color adjustment particles, 30g of alcohol-soluble silicone modified polyurethane resin, 0.1g of adhesion promoter Tech-7121, 0.1g of wetting agent Tech-204E, and 1g of graphene composite antiviral slurry were added. 1500E, 1gPM diluent and 9gDPM diluent were stirred and mixed evenly, and sieved through 400 mesh to prepare a colored heat insulation coating liquid;

[0032] The prepared colored heat-insulating coating liquid is applied to the clean glass surface with a high-density sponge brush at 10°C and 10% humidity. After the surface is dried for 60 minutes and completely cured for 7 days, a colored heat-insulating sun-proof glass coating can be obtained.

[0033] Embodiment 2

[0034] First, a copper-zinc-cesium ion co-doped tungsten oxide / graphene composite thermal insulation powder is prepared: first, a mixture of copper nitrate, zinc nitrate, cesium iodide and ammonium metatungstate with a total mass of 100 g is weighed according to the molar ratio of copper, zinc, cesium and tungsten in the molecular formula of 0.03:0.03:0.32:0.94, crushed and ground evenly, and then slowly added to 300 g of ammonia solution with a pH of 9, ultrasonically stirred for 40 minutes, and then 1 g of reducing dispersant polyvinyl pyrrolidone and 0.02 g of graphene oxide powder are added, and ultrasonic stirring is continued for 80 minutes to obtain a precursor solution, and the precursor solution is transferred to a reactor and heated at 200°C for 18 hours, cooled naturally, filtered, and washed clean to obtain a copper-zinc-cesium co-doped tungsten oxide / graphene composite thermal insulation powder;

[0035] Preparation of copper-zinc-cesium ion co-doped tungsten oxide / graphene composite thermal insulation slurry: using 5g of high polarity dispersant Tech-5011, 12g of alcohol-soluble maleic acid resin, and 50g of propylene glycol methyl ether; in a non-circulating explosion-proof sand mill, using 0.03mm zirconium beads and a linear speed of 11m / s, 24g of composite thermal insulation powder was surface coated and ground to prepare a composite thermal insulation slurry with a D90 of less than 120 nanometers;

[0036] Preparation of color adjustment particles: 6g of inorganic carbon black powder and 6g of phthalocyanine blue were compounded, 3g of dispersant BYK2095, 3g of dispersant UNIQJET 9510, 50g of butanone, 0.2g of pigment synergist Tech-5550, and 3g of aldehyde-ketone resin were added, and ground into a transparent color pigment dispersion in a non-circulating explosion-proof sand mill using 0.05mm zirconium beads and a linear speed of 12m / s, and then 355g of organic UV absorber was added. UV 384-2, dissolve and mix; then use 593g of ethyl acetate to swell the PMMA polymer spherical particles with a particle size of 2μm and a mass of 355g to evenly wrap the color pigment and the organic UV absorber, heat to 54°C in ultrasound, keep for 5h, rotary evaporate the solvent, clean with ethanol, and vacuum dry to obtain color adjustment particles with UV absorption function;

[0037] Finally, 24g of copper-zinc-cesium ion co-doped tungsten oxide / graphene composite insulation slurry, 2g of color adjustment particles, 32g of polysiloxane modified resin, 0.15g of adhesion promoter EL-9041, 0.15g of wetting agent Surfynol 485, and 1.5g of graphene composite antiviral slurry were added. 1515E, 4gPM diluent and 9gDPM diluent were stirred and mixed evenly, and sieved through 400 mesh to prepare a colored heat insulation coating liquid;

[0038] The prepared colored heat-insulating coating liquid is applied to the clean glass surface with a high-density sponge brush at 20°C and 20% humidity. After the surface is dried for 50 minutes and completely cured for 7 days, a colored heat-insulating sun-proof glass coating can be obtained.

[0039] Embodiment 3

[0040] First, a copper-zinc-cesium ion co-doped tungsten oxide / graphene composite thermal insulation powder is prepared: first, a mixture of copper sulfate, zinc sulfate, cesium iodide and ammonium metatungstate with a total mass of 100 g is weighed according to the molar ratio of copper, zinc, cesium and tungsten in the molecular formula of 0.08:0.08:0.36:0.84, crushed and ground evenly, and then slowly added to 300 g of ammonia solution with a pH of 9, ultrasonically stirred for 50 min, and then 1 g of polymer polyol dispersant and 0.045 g of graphene oxide powder are added, and ultrasonic stirring is continued for 100 min to obtain a precursor solution, and the precursor solution is transferred to a reactor and heated at 250° C. for 20 h, naturally cooled, filtered, and washed to obtain a copper-zinc-cesium co-doped tungsten oxide / graphene composite thermal insulation powder;

[0041] Preparation of copper-zinc-cesium ion co-doped tungsten oxide / graphene composite thermal insulation slurry: using 9g of high-polarity dispersant SN-2301, 15g of alcohol-soluble rosin resin, and 50g of propylene glycol methyl ether; in a non-circulating explosion-proof sand mill, using 0.03mm zirconium beads and a linear speed of 11m / s, 30g of composite thermal insulation powder was surface coated and ground to prepare a composite thermal insulation slurry with a D90 of less than 120 nanometers;

[0042] Preparation of color adjustment particles: 8g of iron red powder and 8g of quinacridone red, 4g of dispersant Tech-5010, 4g of dispersant BYK161, 50g of butanone, 0.4g of pigment synergist Tech-5522, and 4g of aldehyde-ketone resin are added, and ground into a transparent color pigment dispersion in a non-circulating explosion-proof sand mill using 0.05mm zirconium beads at a linear speed of 12m / s; then 294g of organic ultraviolet absorber is added. UV-928, dissolved and mixed, and then 392g of PMMA polymer spherical particles with a particle size of 1 μm and a mass of 1 μm swollen by 490g of 4-methyl-2-pentanone were used to uniformly wrap the color pigment and the organic UV absorber, heated to 58°C in an ultrasonic wave, maintained for 5h, and the solvent was evaporated by rotary evaporation, cleaned with ethanol, and vacuum dried to obtain color adjustment particles with UV absorption function;

[0043] Finally, 28g of copper-zinc-cesium ion co-doped tungsten oxide / graphene composite insulation slurry, 3g of color adjustment particles, 35g of alcohol-soluble silicone modified polyurethane resin, 0.2g of adhesion promoter Tech-7121, 0.2g of wetting agent Tech-247, and 2g of graphene composite antiviral slurry were added. 1500E, 6gPM diluent and 9gDPM diluent were stirred and mixed evenly, and sieved through 400 mesh to prepare a colored heat insulation coating liquid;

[0044] The prepared colored heat-insulating coating liquid is applied to the clean glass surface with a high-density sponge brush at 39°C and 69% humidity. After the surface is dried for 40 minutes and completely cured for 7 days, a colored heat-insulating sun-proof glass coating can be obtained.

[0045] Embodiment 4

[0046] First, a copper-zinc-cesium ion co-doped tungsten oxide / graphene composite thermal insulation powder is prepared: first, a mixture of copper acetate, zinc acetate, cesium iodide and ammonium metatungstate with a total mass of 100 g is weighed according to the molar ratio of copper, zinc, cesium and tungsten in the molecular formula of 0.1:0.1:0.4:0.8, crushed and ground evenly, and then slowly added to 300 g of ammonia solution with a pH of 9, ultrasonically stirred for 60 min, and then 1 g of polycaprolactone polyol-polyethyleneimine block copolymer and 0.05 g of graphene oxide powder are added, and ultrasonic stirring is continued for 120 min to obtain a precursor solution, and the precursor solution is transferred to a reactor and heated at 300°C for 24 h, cooled naturally, filtered, and washed to obtain a copper-zinc-cesium co-doped tungsten oxide / graphene composite thermal insulation powder;

[0047] Preparation of copper-zinc-cesium ion co-doped tungsten oxide / graphene composite thermal insulation slurry: using 9g of high-polarity dispersant SN-2301, 15g of alcohol-soluble rosin resin, and 50g of propylene glycol methyl ether; in a non-circulating explosion-proof sand mill, using 0.03mm zirconium beads and a linear speed of 11m / s, 30g of composite thermal insulation powder was surface coated and ground to prepare a composite thermal insulation slurry with a D90 of less than 120 nanometers;

[0048] Preparation of color adjustment particles: 10g iron yellow powder and 10g permanent yellow were mixed, 5g dispersant BYK110, 5g dispersant Tech-5080, 50g butanone, 0.5g pigment synergist Tech-5522, 5g polyamide resin were added, and ground into a transparent color pigment dispersion in a non-circulating explosion-proof sand mill using 0.05mm zirconium beads and a linear speed of 12m / s, and then 256.5g organic UV absorber was added. UV-928, dissolved and mixed, and then swelled with 427.5g of acetone, PMMA polymer spherical particles with a particle size of 2μm and a mass of 427g were used to evenly wrap the color pigment and the organic ultraviolet absorber, heated to 60°C in ultrasound, maintained for 6h, and the solvent was evaporated by rotary evaporation, cleaned with ethanol, and vacuum dried to obtain color adjustment particles with ultraviolet absorption function;

[0049] Finally, 30g of copper-zinc-cesium ion co-doped tungsten oxide / graphene composite insulation slurry, 5g of color adjustment particles, 40g of polysiloxane modified resin, 0.3g of adhesion promoter EL-9041, 0.3g of wetting agent Surfynol 485, and 3g of graphene composite antiviral slurry were added. 1515E, 11g of PM diluent and 9g of DPM diluent were stirred and mixed evenly, and sieved through 400 mesh to prepare a colored heat-insulating coating liquid;

[0050] The prepared colored heat-insulating coating liquid is applied to the clean glass surface with a high-density sponge brush at 39°C and 79% humidity. After the surface is dried for 30 minutes and completely cured for 7 days, a colored heat-insulating sun-proof glass coating can be obtained.

[0051] Table 1 shows the coating performance parameters of Example 1, Example 2, Example 3 and Example 4

[0052] hardness Adhesion color Antiviral activity rate UV Absorption Infrared blocking rate Embodiment 1 6H Level 0 blue 99.5% 99.9% 95% Embodiment 2 6H Level 0 Blue Black 99.9% 99.9% 91% Embodiment 3 6H Level 0 red 99.0% 99.9% 92% Embodiment 4 6H Level 0 yellow 99.3% 99.9% 95%

Claims

1. A method for preparing a colored heat-insulating sun-proof glass coating, characterized in that: The specific steps are as follows: 1) Preparation of copper-zinc-cesium ion co-doped tungsten oxide / graphene composite thermal insulation powder: First, copper salt, zinc salt, cesium iodide, and ammonium metatungstate are weighed, added to a certain mass of ammonia solution with a pH of 9, ultrasonically stirred for a certain time, a reducing dispersant is added, and then graphene oxide powder is added, and ultrasonic stirring is continued for a certain time to obtain a precursor solution, and the precursor solution is transferred to a reactor and heated and kept warm at a certain temperature for a certain time, cooled naturally, filtered, and washed to obtain copper-zinc-cesium co-doped tungsten oxide / graphene composite thermal insulation powder. The copper-zinc-cesium co-doped tungsten oxide is expressed as Cu a Zn b Cs c W 1-a-b O3, wherein 0<a≤0.1, 0<b≤0.1, 0.3≤c≤0.4; the mass ratio of the total weight of copper salt, zinc salt, cesium iodide and ammonium metatungstate, pH=9 ammonia solution, reducing dispersant and graphene oxide powder is 1:3:0.1:(0.001~0.005); 2) Preparation of copper-zinc-cesium ion co-doped tungsten oxide / graphene composite thermal insulation slurry: using a high-polarity dispersant, an alcohol-soluble grinding resin, and a solvent, the composite thermal insulation powder is surface coated and ground to form a composite thermal insulation slurry, wherein the high-polarity dispersant is one of the polymer dispersants SN-2301, Tech-5011, and SN-1008A with an acidic group or a combination thereof; the alcohol-soluble grinding resin is one of the alcohol-soluble rosin resin, the alcohol-soluble maleic acid resin, and the alcohol-soluble aldehyde-ketone resin or a combination thereof; the solvent is one of ethanol and propylene glycol methyl ether; the mass ratio of the composite thermal insulation powder, the high-polarity dispersant, the alcohol-soluble grinding resin, and the solvent is (20-30): (4-9): (10-15): 50; the zirconium beads are selected to have a diameter of less than 0.1 mm, and the sanding line speed is less than 13 m / s; 3) Preparation of color-adjusting particles: compounding an inorganic color powder and an organic color powder, adding dispersant A, dispersant B, an organic solvent, a pigment synergist, and a grinding resin to grind into a transparent color pigment dispersion, then adding an organic ultraviolet absorber, dissolving and mixing, and then uniformly wrapping the color pigment and the organic ultraviolet absorber with PMMA polymer swelled with a swelling agent. The temperature is raised to a certain temperature in an ultrasonic wave and swelled for a certain time, and the solvent is evaporated by rotary evaporation. The ethanol is cleaned and vacuum dried to obtain color-adjusting particles with ultraviolet absorption function, wherein the inorganic nano color powder is one of carbon black, cobalt blue, iron red and iron yellow; the organic color powder is one of phthalocyanine blue, quinacridone red and permanent yellow; the dispersant A is one of BYK110, BYK-2095 and Tech-5010; the dispersant B is Tech-5080, UNIQJET 9510 and BYK161; the organic solvent is one of ethyl acetate, butanone and ethanol; the pigment synergist is one of Tech-5522 and Tech-5550; the grinding resin is one of polyamide resin and aldehyde-ketone resin; the mass ratio of the inorganic nano color powder, the organic color powder, the dispersant A, the dispersant B, the organic solvent, the pigment synergist and the grinding resin is (5-10): (5-10): (2-5): (2-5): 50: (0.1-0.5): (2-5); the zirconium beads are selected to have a diameter of less than 0.1 mm and a sanding line speed of less than 13 m / s; the PMMA polymer particles are selected to have a particle size of 1 to 2 microns; the swelling agent is one of alkylphenol polyoxyethylene ether, propylene glycol methyl ether, butanone, ethyl acetate, 4-methyl-2-pentanone, acetone, dimethyl sulfoxide or a combination thereof; the organic ultraviolet absorber is UV-928 and UV 384-2; the mass ratio of the transparent color pigment dispersion, swelling agent, PMMA polymer particles and organic ultraviolet absorber is (5-10):50:(20-50):30; in the step 3), the temperature is ultrasonically raised to 50-60°C for 4-6 hours; 4) Finally, the copper-zinc-cesium ion co-doped tungsten oxide / graphene composite thermal insulation slurry, color adjustment particles, special resin, adhesion promoter, wetting agent, graphene composite antiviral slurry, and diluent are stirred and mixed evenly, sieved, and a colored thermal insulation coating liquid is prepared. In step 4), the special resin is an alcohol-soluble silicone-modified polyurethane resin; the adhesion promoter is one of Tech-7121 and EL-9041; the wetting agent is one of acetylene glycol wetting agents Tech-204E, Surfynol 485, and Tech-247; the graphene composite antiviral slurry is an alcohol slurry. 1500E or 1515E; the diluent is one of PM and DPM or a combination thereof; the copper-zinc-cesium co-doped tungsten oxide / graphene composite thermal insulation slurry: color adjustment particles: special resin: adhesion promoter: wetting agent: graphene composite antiviral slurry: diluent = (20-30): (1-5): (30-40): (0.1-0.3): (0.1-0.3): (1-3): (10-20); 5) Apply the prepared colored heat-insulating coating liquid to the clean glass surface with a high-density sponge brush under certain temperature and humidity requirements, and bake at room temperature or 150° C. to completely cure to obtain a colored heat-insulating sunscreen glass coating. The construction temperature of step 5) is 10-40° C. and the humidity is less than 80%.

2. The method for preparing a colored heat-insulating sun-proof glass coating according to claim 1, characterized in that: The copper salt is one of copper acetate, copper nitrate and copper sulfate; the zinc salt is one of zinc acetate, zinc nitrate and zinc sulfate; the ultrasonic stirring time is 30 to 60 minutes; the reducing dispersant is one of polycaprolactone polyol-polyethyleneimine block copolymer, polyvinyl pyrrolidone and polymer polyol; the continued ultrasonic stirring time is 60 to 120 minutes; the heating temperature of the reactor is 180 to 300°C, and the heat preservation is 12 to 24 hours.

Citation Information

Patent Citations

  • Colored transparent heat insulation glass coating and preparation method thereof

    CN102391778A

  • Water-based transparent pearlescent paint and preparation method thereof

    CN106566336A

  • Preparation method of graphene-containing transparent thermal insulation coating for glass, product prepared with method and application of coating

    CN107629666A

  • Efficient heat-insulating glass coating material and preparation method therefor

    CN110804390A

  • Copper-zinc-doped phosphate antibacterial agent, preparation method thereof and application of copper-zinc-doped phosphate antibacterial agent in antibacterial plastic

    CN115281215A